An Exploratory Study on Current Corporate Governance among Practitioners in Malaysian Public Listed Companies - An Introduction to Quantum Governance - Arulanandam, Benedict Valentine* (Hampstead Psychological Associates, 2020)
Over the last decade, corporate governance was heightened by many incidences that questioned the governance of corporations globally. Simultaneously, Malaysia has also taken measures to address corporate governance issues within corporations. These measures have indeed borne much fruit and have helped in the improvement of governance structure in Malaysian companies, especially public listed firms. There have been several studies globally and domestically addressing some issues in corporate governance. However, there were hardly any relevant studies pertaining to the perceptions of corporate governance by senior managers of public listed companies in Malaysia who are the practitioners. This study undertakes to explore the perception of the current corporate governance structure in Malaysia and to a large extent, to discover their understanding of the corporate governance mechanism within Malaysian public listed companies. As this study is an exploratory study with a realism and a positivist philosophical stance, a qualitative research methodology was used. Face-toface in-depth interview with an interview guide and focus groups were used, which were effective means in acquiring the perspectives and the paradigms of the participants. For the purpose of this study, participants who are working in public listed companies in the Main Board of Bursa Malaysia, holding the position of senior managers and above, were selected as the population, as they are practitioners in a variety of industries. The findings revealed that the respondents perceived corporate governance as a mechanical stance, from a stand point of legal (law), system (methodology) and guide (set of frameworks) through which decisions were made. The respondents agreed that corporate governance regulations were merely “cut and pasted” from an external source, which means that the form supersedes the substance in corporate governance. Thus, the respondents revealed that it has resulted in a mismatch. This study reveals the necessity to address the fundamentals of corporate governance.